Mammalian Browsers Disrupt Eco‐Evolutionary Dynamics in a Forest Tree Restoration Planting - João Costa e Silva; Brad M. Potts; Peter A. Harrison (Evolutionary Applications)
ABSTRACT Native and restored forests are increasingly impacted by pests and diseases, including large herbivores. While community‐ and species‐level impacts of these tree enemies are often well‐documented, there is little understanding of their influence on finer‐scale eco‐evolutionary processes. We here study the influence of large‐mammal herbivory on the survival and height growth of trees in a mixed species restoration planting of the Australian forest trees, Eucalyptus ovata and E. pauciflora, in Tasmania, Australia. Common‐garden field trials mixing the two species were compared in adjacent unbrowsed (fenced) and browsed (unfenced) plantings. The browsed planting was exposed to mammal browsing by native marsupials, as well as feral introduced European fallow deer (Dama dama). Each tree species was represented by open‐pollinated families from 22 paired geographic areas, allowing the assessment of the effects of browsing on the species and population differences, as well as on family variation within each species. In the browsed planting, a marked reduction in species and population differences, as well as in family variance, was observed for both height growth and survival. The pattern of height growth and survival of the populations of both species also differed between browsing regimes, with significant changes of climate relationships involving both focal tree attributes detected. Our results argue for a major disruption of the eco‐evolutionary dynamics of restored forests in the presence of browsing by large mammalian herbivores, at the observed period of the tree life cycle. Importantly for forest restoration and conservation in the face of global change, our results challenge the choice of tree populations for translocation based solely on predicted or observed relationships of their home‐site climate with current and predicted future climates of the restoration sites, while emphasising the need for genetic diversity to provide future resilience of restored forests to both biotic and abiotic stresses.